The incidence, intensity and host morbidity of human parasitic protozoan infections in gastrointestinal disorder outpatients in Buea Sub Division, Cameroon - Judith Veshiyi Mbuh; Helen N. Ntonifor; James T. Ojong (Journal of Infection in Developing Countries)
Background: Numerous protozoans inhibit the gastrointestinal tract of humans with the majority being either non-pathogenic commensals or of a type that may result in mild disease. However, some of these organisms can cause severe diseases under certain circumstances while others may become highly virulent and invasive causing potentially lethal systemic disease. This study investigated the prevalence, intensity and host morbidity of human intestinal protozoan infections in individuals living in the Buea Sub-Division, Cameroon.